The Influence of a Scientific Investigation Workshop on In-service Biology Teachers’ Attitudes Towards Scientific Investigations - Naudé, Shani; Pretorius, Jannie (Research in Social Sciences and Technology, 2024)
Biology teachers’ attitudes play a vital role in successful scientific investigations. Some biology teachers situated in the central part of South Africa experience challenges that include a lack of the necessary scientific knowledge and skills, which hinders the presentation of scientific investigations. These challenges adversely influence these biology teachers’ attitudes towards conducting scientific investigations. The result is that they conduct the minimum number of investigations with their learners, or don’t conduct them at all. Professional, in-service training workshops allow biology teachers to develop the necessary scientific knowledge and skills to successfully conduct scientific investigations. This study aimed to understand how a scientific investigation workshop affected biology teachers’ attitudes by measuring the ABC attitude model’s affective, cognitive and behavioural components. Likert-type, five-point scale items were used for the 20 pre-surveys and the same for the 20 post-surveys that were completed and collected for analysis. This research provided information on how vital in-service training programmes such as this scientific investigation workshop are in fostering positive attitudes toward scientific investigations amongst biology teachers. The findings that emerged from this study imply that implementing this scientific investigation workshop has developed biology teachers’ confidence in their science skills and knowledge to facilitate scientific investigations. The findings also indicate that this workshop caused a significant improvement in teachers’ intended behaviours in implementing scientific investigations in the science classrooms, as they gained valuable knowledge and skills regarding the science apparatus and the use thereof in conducting scientific investigations.